On the mean square of the Epstein zeta-function - Savastru, O.V.; Varbanets, P.D. (Algebra and Discrete Mathematics, 2005)
We consider the second power moment of the Epstein zeta-function and construct the asymptotic formula in special
case, when ϕ₀(u,v) = u² + Av² , A > 0, A ≡ 1, 2(mod 4) and
ϕ0(u,v) belongs to the one-class kind G₀ of the quadratic forms of
discriminant −4A.